Development of Automated Chick Counting Machine using Mechatronics - Jan Gabriel U. Bernardo; Ainee R. Adrias; Wilfredo G. Tuso III (Southeast Asian Journal of Science and Technology, 2023)
An automated chick counting machine using mechatronics was developed that aimed to reduce counting errors, improve counting speed, and acknowledge chick welfare. The machine performance was evaluated in terms of theoretical capacity, actual capacity, machine efficiency, power consumption, accuracy, and precision at different linear belt speeds LBS1, LBS2, and LBS3 of 10.6 cm/s, 16.0 cm/s, and 21.3 cm/s, respectively. The automated chick counting machine has an overall dimension (length, width, and height) of 1350 mm, 465 mm, and 756 mm, respectively. It has a mainframe, loading platform, chick conveyor line, side guards, counting chamber, and slide unit as its components. The samples used were day-old broiler chicks. The machine performance was tested in a single-factor experiment in a completely randomized design (CRD) with three (3) replications for each linear belt speed (10.6, 16.0, and 21.3 cm/s). Results showed that the machine attained a theoretical capacity, actual capacity, machine efficiency, power consumption, accuracy, and precision of 1367 - 2475 chicks/h, 1159 - 2106 chicks/h,  84.94 - 85.35%, 0.51 - 0.81 W-h, 91.67 - 95%, and 0.95 - 0.98, respectively. One-way ANOVA showed significant differences on theoretical capacity, actual capacity, and power consumption at different linear belt speeds. The fabrication and machine cost was Php 26,551 and Php 44,079, respectively.